Association Between Hospital-Level Obstetric Quality Indicators and Maternal and Neonatal Morbidity. Issue 2 (February 2015) - Howell, Elizabeth A.; Zeitlin, Jennifer; Hebert, Paul L.; Balbierz, Amy; Egorova, Natalia
Abstract : ABSTRACT: Obstetric complications persist, with severe maternal and neonatal complications occurring in low-risk term infants. Complication rates among hospitals vary and indicate that the quality of obstetric care can be improved. The Joint Commission recommends 2 perinatal quality measures that address important aspects of obstetric care: elective deliveries performed before 39 weeks' gestation and cesarean deliveries (CDs) performed in low-risk nulliparous women. How well hospital performance on these quality indicators correlates with maternal or neonatal morbidity is unknown. This population-based observational study was undertaken to determine whether use of these 2 quality measures was associated with severe maternal or neonatal morbidity in New York City hospitals. Birth certificate and discharge data sets from 2010 were linked, and delivery hospitalizations were identified. Published algorithms were used to identify severe maternal morbidity for delivery associated with a life-threatening complication or lifesaving procedure and for neonatal morbidity for birth-associated complications. The first quality measure was elective, nonmedically indicated deliveries at 37 weeks or more and less than 39 weeks' gestation. The second measure, CDs in low-risk women, was the proportion of CDs among nulliparous patients with singleton vertex deliveries at 37 weeks or more. Rates of elective deliveries and low-risk CDs were calculated for each hospital. Mixed-effects logistic regression models were used to generate risk-standardized severe maternal and neonatal morbidity rates at term for each hospital, with risk adjustments for patient sociodemographic/clinical and hospital-level characteristics. The final sample included 115, 742 deliveries, of which 2732 (2.4%) were associated with severe maternal morbidity. After exclusions of multiple births, those with congenital anomalies, and births at less than 37 weeks, the final sample included 103, 416 newborns, of whom 8057 (7.8%) evidenced neonatal morbidity. Hospital performance per 100 deliveries ranged from 15.5 to 41.9 for elective deliveries before 39 weeks, from 11.7 to 39.3 for age-standardized rates of CDs in low-risk nulliparous women, from 0.9 to 5.7 for risk-standardized severe maternal morbidity rates, and from 3.1 to 21.3 for risk-standardized neonatal morbidity rates. Both quality measures were correlated with each other (Spearman ρ = 0.45; P = 0.003). Severe maternal morbidity and neonatal morbidity at term were also correlated (Spearman ρ = 0.39; P = 0.01). Hospital rankings on both quality measures were not associated with hospital rankings for maternal or neonatal morbidity. Rankings were similarly discordant for neonatal morbidity. Nonparametric correlations between obstetric quality indicators and maternal and neonatal morbidity were not significant (Spearman ρ = −0.01, P = 0.94 for CD and maternal morbidity; Spearman ρ = −0.10, P = 0.52 for CD and neonatal morbidity; Spearman ρ = 0.14, P = 0.39 for elective delivery and maternal morbidity; Spearman ρ = −0.14, P = 0.39 for elective delivery and neonatal morbidity). In mixed-effects models including both quality measures, neither indicator was associated with severe maternal morbidity; the risk ratio for elective delivery was 1.00 (95% confidence interval, 0.97–1.03) and 0.98 for low-risk CDs (95% confidence interval, 0.95–1.01). In models including patient-level variables and patient-level and other hospital-level variables, risk ratios for both quality measures remained unchanged. For severe maternal morbidity, the intraclass correlation coefficient was 28% in the unadjusted model; after adjusting for patient characteristics, intraclass correlation coefficient was 22%. Findings were similar in the models for the 2 measures and neonatal morbidity. Severe maternal and neonatal morbidities at term remain important health issues. However, morbidity rates were not correlated with the performance measures that assess hospital-level obstetric quality of care. The need for an expanded array of obstetric quality measures is apparent based on these results.